2013
DOI: 10.1073/pnas.1314045110
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the utility of coevolution-based residue–residue contact predictions in a sequence- and structure-rich era

Abstract: Significance We develop an improved method for predicting residue–residue contacts in protein structures that achieves higher accuracy than previous methods by integrating structural context and sequence coevolution information. We then determine the conditions under which these predicted contacts are likely to be useful for structure modeling and identify more than 400 protein families where these conditions are currently met.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
789
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 653 publications
(806 citation statements)
references
References 24 publications
16
789
0
1
Order By: Relevance
“…DCA has successfully been used to identify intradomain (23)(24)(25)(26)(27) and interdomain (16,17,23,28) contacts in proteins, including the prediction of a transient HK/RR complex that is within crystallographic accuracy of the experimentally determined structure (6). Other recent statistical methods have also been applied to sequence coevolution to explore a diverse range of topics ranging from protein structure and function (29)(30)(31)(32)(33)(34)(35) to the evolutionary fitness of HIV (36). Extending the predictive power of DCA beyond structure prediction, a recent study by Procaccini et al (37) demonstrated that the direct couplings inferred from DCA can be used to quantify interaction specificity among HK and RR proteins.…”
Section: Significancementioning
confidence: 99%
“…DCA has successfully been used to identify intradomain (23)(24)(25)(26)(27) and interdomain (16,17,23,28) contacts in proteins, including the prediction of a transient HK/RR complex that is within crystallographic accuracy of the experimentally determined structure (6). Other recent statistical methods have also been applied to sequence coevolution to explore a diverse range of topics ranging from protein structure and function (29)(30)(31)(32)(33)(34)(35) to the evolutionary fitness of HIV (36). Extending the predictive power of DCA beyond structure prediction, a recent study by Procaccini et al (37) demonstrated that the direct couplings inferred from DCA can be used to quantify interaction specificity among HK and RR proteins.…”
Section: Significancementioning
confidence: 99%
“…contacts between bacterial signal transduction proteins, to help to assemble protein complexes (15,16) and shed light on interaction specificity (17,18). The applicability of DCA and related coevolutionary approaches (19,20) to protein−protein interactions far beyond the signaling system has been recently established (21,22).…”
mentioning
confidence: 99%
“…This capability is especially consequential for multisegment TERMs, because it means that segments distant in sequence can be predicted to be adjacent in space-a major challenge in structure prediction. Significant strides toward addressing this challenge have recently emerged from prediction of contacts based on evolutionary covariation (70,71), but, importantly, such prediction is only applicable to native proteins, and especially those with available deep MSAs. On the other hand, TERM-based mining appears to be quite applicable to de novo proteins and requires no homology (Fig.…”
Section: Discussionmentioning
confidence: 99%